2021
DOI: 10.18632/aging.202749
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics study of protein inhibitor of activated STAT1 in mouse hippocampal neuronal cells revealed by RNA sequencing

Abstract: Protein inhibitor of activated STAT1 (PIAS1), a small ubiquitin-like modifier (SUMO) E3 ligase, was considered to be an inhibitor of STAT1 by inhibiting the DNA-binding activity of STAT1 and blocking STAT1-mediated gene transcription in response to cytokine stimulation. PIAS1 has been determined to be involved in modulating several biological processes such as cell proliferation, DNA damage responses, and inflammatory responses, both in vivo and in vitro . However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Our study showed that FOSL1 and TRIP10 were among the genes enriched in the TNFA via the NFKB pathway, and their expression was associated with ICAM-1. TRIP10 was previously included in an AD network derived from multi-omic integration [59] and FOSL-1 was identified in conjunction with PIAS1, a protein associated with AD and inflammatory response [60]. We identified VASP and C4B in an APOE genotype-specific co-expressed gene network in the brain that was reproduced in the blood, and the expression of these genes was significantly associated with levels of multiple vascular damage proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed that FOSL1 and TRIP10 were among the genes enriched in the TNFA via the NFKB pathway, and their expression was associated with ICAM-1. TRIP10 was previously included in an AD network derived from multi-omic integration [59] and FOSL-1 was identified in conjunction with PIAS1, a protein associated with AD and inflammatory response [60]. We identified VASP and C4B in an APOE genotype-specific co-expressed gene network in the brain that was reproduced in the blood, and the expression of these genes was significantly associated with levels of multiple vascular damage proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed that FOSL1 and TRIP10 were among the genes enriched in the TNFA via NFKB pathway, and their expression was associated with ICAM-1. TRIP10 was previously included in an AD network derived from multi-omic integration [54] and FOSL-1 was identified in conjunction with PIAS1, a protein associated with AD and inflammatory response [55]. We identified VASP and C4B in an APOE genotype-specific co-expressed gene network in brain that was reproduced in blood, and expression of these genes was significantly associated with levels of multiple vascular damage proteins.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the authors constructed a regulatory network for PIAS1 overexpression, including nuclear receptor subfamily 3 group C member 2 (NR3C2), which directly interacts with PIAS1. However, further studies on these downstream targets are necessary [ 84 ].…”
Section: E3s Involved In Neurodegenerative Diseasesmentioning
confidence: 99%